2008
DOI: 10.1177/1077801208329387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Types, and Pattern of Intimate Partner Violence Among Pregnant Women in Lima, Peru

Abstract: This study assesses the prevalence, types, and pattern of intimate partner violence (IPV) during lifetime and current pregnancy for 2,392 women in Lima, Peru. The reported lifetime prevalence of any IPV (physical, sexual, or emotional) is 45.1%. For women who experienced abuse, the prevalence of lifetime physical, emotional, and sexual IPV is 34.2%, 28.4%, and 8.7%, respectively. Older (>/= 30 years), unmarried, employed, and economically disadvantaged women and those with little education are more likely to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
75
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 84 publications
15
75
2
5
Order By: Relevance
“…Although estimates concerning emotional and sexual violence during pregnancy vary, there does appear to be a common pattern: the prevalence of emotional violence is generally greater than the prevalence of physical violence. 13 In this study, 36.8% (n=173) pregnant women reported that they sometimes experienced domestic violence during their pregnancy which is consistent with the study done among 1215 women presenting to abortion clinics in China by Wu et al 14 which showed that majority of the women regularly experienced domestic violence, including during their current pregnancies. In this study, 43.2% (n=118) pregnant women were threatened of remarriage or sending back to parents' home and it was the most common emotional violence experienced.…”
Section: Discussionsupporting
confidence: 79%
“…Although estimates concerning emotional and sexual violence during pregnancy vary, there does appear to be a common pattern: the prevalence of emotional violence is generally greater than the prevalence of physical violence. 13 In this study, 36.8% (n=173) pregnant women reported that they sometimes experienced domestic violence during their pregnancy which is consistent with the study done among 1215 women presenting to abortion clinics in China by Wu et al 14 which showed that majority of the women regularly experienced domestic violence, including during their current pregnancies. In this study, 43.2% (n=118) pregnant women were threatened of remarriage or sending back to parents' home and it was the most common emotional violence experienced.…”
Section: Discussionsupporting
confidence: 79%
“…Some Brazilian and international studies report that the prevalence of psychological, physical and/or sexual violence during pregnancy ranges from 3.2% up to 43.1% 11,14 . High and varying rates of psychological violence during pregnancy were observed, ranging from 16% to 46.9% 15,16 , physical violence from 3.6% to 21% 17,18 and sexual violence from 3% to 9.1% 16,19 . There are few Brazilian studies addressing IPV among pregnant and postpartum women, but the rates of prevalence of psychological, physical and/or sexual violence range from 6.5% to 20% [16][17][18][19][20][21] .…”
Section: Methodsmentioning
confidence: 99%
“…High and varying rates of psychological violence during pregnancy were observed, ranging from 16% to 46.9% 15,16 , physical violence from 3.6% to 21% 17,18 and sexual violence from 3% to 9.1% 16,19 . There are few Brazilian studies addressing IPV among pregnant and postpartum women, but the rates of prevalence of psychological, physical and/or sexual violence range from 6.5% to 20% [16][17][18][19][20][21] . Based on the hypothesis that IPV increases the chances that severe maternal morbidity will occur, this study's objectives were to evaluate the effect of intimate partner violence (psychological, physical and/or sexual) during the current pregnancy on the outcome 'severe maternal morbidity' and to analyze the factors associated with injuries: IPV and severe maternal morbidity.…”
Section: Methodsmentioning
confidence: 99%
“…In a study in Peru [42], physical violence has estimated about 34.2%. Also, another study in Nigeria [43] has classified the physical violence as a prevalent violence against women (55.6%). In a study by Clark and colleagues [44], physical violence has classified in second place (31.2%).…”
Section: Discussionmentioning
confidence: 99%